2018
DOI: 10.3390/su10020366
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Energy Transition through Energy Commons: An Application of Socio-Ecological Systems Framework for Integrated Community Energy Systems

Abstract: Integrated Community Energy Systems (ICES) are an emerging local energy system focusing on the collective use of distributed energy resources (DER). These socio-technical systems (STSs) have a high potential to advance the transition towards socially inclusive, environmentally-friendly energy systems and to stimulate the local economy. While there is an analogy between energy in ICES and other common goods such as natural resources, it is not clear to what extent the existing theoretical framework for Socio-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 24 publications
0
40
0
3
Order By: Relevance
“…Article contributions to this special issue came from a wide set of academic disciplines from the behavioral and social sciences, like law [49,62], psychology [46,50,51,56], sociology [45,53], governance and policy studies [54,57,59], economics [48,60,63], econometrics [61], anthropology [47,52], ethics [56], geography [55,64], and environmental sciences [58].…”
Section: Background Characteristics Of Article Contributions To This mentioning
confidence: 99%
See 1 more Smart Citation
“…Article contributions to this special issue came from a wide set of academic disciplines from the behavioral and social sciences, like law [49,62], psychology [46,50,51,56], sociology [45,53], governance and policy studies [54,57,59], economics [48,60,63], econometrics [61], anthropology [47,52], ethics [56], geography [55,64], and environmental sciences [58].…”
Section: Background Characteristics Of Article Contributions To This mentioning
confidence: 99%
“…In their contribution Acosta et al [63] introduce Integrated Community Energy Systems (ICES) and the role of community energy therein. ICES are an emerging form of local energy systems focusing on the collective use of distributed energy resources.…”
Section: Insights On Social Innovationmentioning
confidence: 99%
“…Energy systems already include energy resources, technologies, and socio-economic processes, while socio-ecological systems more explicitly include governance systems, and actors, in addition to resource systems (energy, water, air, land, biodiversity) and their units [72]. Considering energy in the context of socio-ecological systems may generate new insights, such as the role of policies affecting household consumption, energy demand, and climate change [73][74][75].…”
Section: Establish Framework For Comparisonmentioning
confidence: 99%
“…Although von Wirth et al [13] suggested using geographical information systems to quantify the potential for the local acceptance of DESs with respect to technical, spatial, and social aspects, this is not applicable here because the case area does not contain any inhabitants and the city owns the land. In a socio-ecological system framework for ICESs by Acosta et al [40], the research was grounded in the early design phase, where the discussion moved from the initial phase to soft variables. In negotiation terms, this phase addresses the mapping of interests without premature commitment to the potential solutions [41].…”
Section: Research Questionmentioning
confidence: 99%